Arthroscopic Debridement for Mucoid Degeneration of Anterior Cruciate Ligament - A Single Institution Experience from Nepal - Shrestha, R; Khadka, SK; Maharjan, S; Basi, A; Dahal, A; Chaudhary, A; Acharya, SP; Malla, M (Kathmandu University Medical Journal, 2023)
Background Mucoid degeneration of anterior cruciate ligament is characterized by infiltration of mucoid-like material scattered throughout the anterior cruciate ligament substance. It is an uncommon condition, but previously, underdiagnosed or often misdiagnosed as an anterior cruciate ligament tear. Objective To present our early experiences with mucoid degeneration of anterior cruciate ligament in last five years in terms of clinical presentation and the outcomes of arthroscopic management. Method This was a retrospective descriptive cross-sectional study on patient who received arthroscopic debridement for mucoid degeneration of anterior cruciate ligament in Dhulikhel Hospital over five years period (2017 May to 2022 April). Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scale that has been translated and validated to be used in local (Nepali) language and context was used for evaluation of outcome evaluation. Result Twenty-one patients of mean age 44.21 years, predominantly females (18), were managed in five years period. The mean Western Ontario and McMaster Universities Osteoarthritis Index score was 16.33±10.47 with a range of 0 to 36 (11.57 to 21.09 at 95% confidence interval). The mean Western Ontario and McMaster Universities Osteoarthritis Index score converted on a scale of 0 to 100 was 17. Thirteen patients had isolated Mucoid degeneration of anterior cruciate ligament whereas nine others had associated either meniscal tear or chondral lesions. Conclusion Mucoid degeneration of anterior cruciate ligament could be a cause of knee pain in middle-aged patients and arthroscopic debridement can improve the patient’s symptoms and provide a good functional outcome.